Konflik Psikologis Tokoh Utama dalam Novel Arini Masih Ada Kereta yang Akan Lewat Karya Mira W - Nurhasanah, Nurhasanah; Effendi, Darwin; Utami, Puspa Indah (UNIB Press, 2020)
The purpose of this study was to describe the psychological conflicts contained in the novel Arini Masih Ada Kereta yang Lewat by Mira W. The research method used is descriptive method. The data source in the study was the novel Arini Masih Ada Kereta yang Lewat by Mira W. consisting of 232 pages, a book thickness of 20 cm, published in 2018 by PT Gramedia Pustaka Utama. The collection technique uses literature study techniques, reading techniques, and note taking techniques. While the data analysis technique used content analysis techniques. Based on the research results, it shows that the psychological conflicts built in the novel Arini Masih Ada Kereta yang Lewat by Mira W are in the form of internal conflict and external conflict. Internal conflict, namely the main character Arini felt a raging feeling shortly after the feeling of happiness when she saw the baby she had given birth to. Then, the external conflict, namely the character Arini knows a reality that Helmi said, such as a slap for Arini, a child who he thought had died was still alive and Helmi who took care of him.